The relation between patent processus vaginalis defined by ultrasonography and the clinical hernia: Second step study - Kazez, Ahmet; Parmaksiz, M. Ergun; Akfirat, Murat; Apak, Sami (My University, 2001)
Aim: In the present study, the clinical meaning of the patent processus vaginalis (PPV) as defined by ultrasonography (US) at the asymptomatic side, and its validity for the contralateral exploration were studied. Method: From Dec 1998 to Jan 2000, 29 children who had unilateral inguinal hernia brought to our clinic were included in this study. Bilateral inguinal US was applied to all of them by an experienced radiologist. They underwent operation only at the history and clinically positive sides. They were kept under follow-up for 11 months on average, and before finishing the study they were re-assessed. Results: Average age of the patients was 20.4 months (50 days-4 years). In all the 29 patients operated at the symptomatic side, processus vaginalis was determined through US. The patency was measured between 3.5-3.9 mm in seven of these cases, and remaining patients presented patency was above 4 mm. In the opposite groins study, in 10 cases as patent processus vaginalis (range 2-3 mm) and in only one case as inguinal hernia (4.1 mm) were assessed by US. However, during control period in the 11 cases, no clinical hernia was observed. According to these results, in terms of clinical meaning, the sensitivity of the PPV criterion of the US is 50 %, its specificity 67 %, its positive predictive value 50 % and the negative predictive value is 50 %, respectively. Conclusions: US is a reliable technique for the identification of PPV. Although PPV can be observed by US, clinical finding of hernia might not be present. Contralateral exploration with US can reduce negative surgical exploration rate.
Ultrasonografinin tanimladi?i patent prosessus vaginalis ile herni ilişkisi: İkinci basamak çalişma
Keywords: Child; Inguinal hernia; Ultrasonography